Are Prophylactic Systemic Antibiotics Necessary with Nasal Packing? A Systematic Review. Issue 4 (July 2017) - Lange, Jessica L.; Peeden, Erin H.; Stringer, Scott P.
Background: The use of prophylactic systemic antibiotics with nasal packing has been a controversial topic. There are few evidence-based studies to determine the need for prophylactic systemic antibiotics. We performed a systematic literature review to determine the role of prophylactic systemic antibiotics with nasal packing in the prevention of toxic shock syndrome and local nasal infections. Objective: The purpose of this study was to perform a systematic literature review to determine the role of prophylactic systemic antibiotics with nasal packing in the prevention of toxic shock syndrome and local nasal infections. Methods: A search for studies that reviewed the efficacy of prophylactic systemic antibiotics in the prevention of toxic shock or nasal infections and/or sinusitis for patients with nasal packing for epistaxis and postoperative septoplasties was performed. This was conducted in a number of medical literature data bases by following the methods of the 2009 Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Only English publications and human studies that were randomized control trials, quasi-randomized control trials, controlled clinical trials, retrospective studies, and case series were included. Results: Six studies, with a total of 990 patients, met the inclusion criteria for the review and were included. Primary outcomes were signs and symptoms of nasal or sinus infections in patients who underwent nasal packing for epistaxis or septoplasty. There were no reports of toxic shock syndrome in any patients, and there was no statistical difference in purulent drainage in patients who had septoplasty (9.9 versus 11.2%) treated with or without antibiotics. Conclusion: There is a paucity of literature that reviewed the need for prophylactic systemic antibiotics with nasal packing. The available literature does not show a significant benefit to the use of antibiotics with nasal packing, but the studies were underpowered to detect such a difference. One must consider the associated risks of prophylactic antibiotics to the patient as well when deciding to prescribe prophylactic antibiotics.